High School Students’ Awareness of Environmental Issues in Indonesia: A Mini Review - Keisya Auliayanti; Eko Weni; Isti Faizati Zainiyah; Michael Biney; Shivi Shrotriya (Tecno Scientifica Publishing, 2025)
There were several environmental challenges in urban areas, especially related to solid waste management. Learning and community engagement in schools were crucial to promoting sustainability and environmental awareness. A mini-review was conducted to explore the potential of student-led efforts to divert organic waste, specifically fallen dry leaves. Using the Theory of Planned Behavior (TPB), we examined how environmental awareness impacted pro-environmental behavior. Students contributed to sustainable waste management by becoming aware of environmental issues and taking action. Educating students about environmental issues played a crucial role in cultivating environmental awareness. By integrating environmental concepts into the curriculum and organizing extracurricular activities, schools prepared students to address environmental challenges. Even after specific programs such as Adiwiyata were concluded, challenges remained in sustaining environmental initiatives. Schools needed to prioritize environmental education, engage students in active participation, and create an environment that fostered a sustainable culture to ensure long-term impact. Schools made a real difference to the environment by managing organic waste and promoting environmental awareness.